Suplementação com sais de cálcio de ácidos graxos para vacas de corte mantidas em pastagem natural durante o período pré e/ou pós-parto - Silveira, Magali Floriano da (2010)
The objective of this study was to evaluate whether supplementation with calcium salts of fatty acids (CSFA) during to pre and/our postpartum affects production and composition of milk, metabolites blood, productive and reproductive performance from beef cows of different genetic groups maintained on native pasture, and performance of this calves. Were used 86 of crossbred Charolais Nellore cows, distributed into the following supplement treatments: PRE: supplemented with CSFA during 45 days prepartum; PREPOS: supplemented with CSFA during 45 days prepartum and 63 days postpartum; POS: supplemented with CSFA during 63 days postpartum; PN: without supplementation. The data were submitted to analysis of variance, the model included cow age and birth order as covariates and the effects of supplementation, cow genetic group, period and the interactions among these factors. There was no significant interaction between the factors evaluated. Cows supplemented with fat protected in the prepartum and/or postpartum showed milk production and productions of components of the milk similar. Crossbreed Nellore cows showed milk with higher lactose content. The supplementation with calcium salts of fatty acids during the pre and/or postpartum non affect the metabolites blood from beef cows. The cholesterol content increase and triglycerides and urea decreased linearly until the end of the experiment. The supplementation with by-pass fat non affect the performance of the calves. Adults cows produced calves with superior performance to produced by first calf and young cows until the 7 months of age. Crossbreeds Nellore cows produced calves with average weight daily gain (GMD) superior from 21 to 42 days of age in relation to crossbreed Charolais cows. The supplementation with fat protected in pre and/or postpartum non affect the productive and reproductive performance from cows. The supplementation great the calving interval. Crossbreed Charolais cows showed higher weight and GMD in relation to croosbreed Nellore cows.